Digital literacy in basic education in Mexico: documentary analysis of the curriculum - Reyes, William (IE Revista de Investigación Educativa de la REDIECH, 2021)
This research begins from the analysis of the archives that make up the curriculum of basic education in the United Mexican States, to determine the degree of integration of digital alphabetization (DA). To carry out this research, nine dimensions were defined, and indicators (keywords) established that served as search terms in official documents. From the analyzed records was observed that all the dimensions of digital alphabetization considered were found in the basic curriculum level, critical thinking being the dimension with the greatest presence and computational thinking the one with the least presence. The results obtained allow us to affirm that digital alphabetization is among the points considered important in basic education.